City politics under austerity in Greece: Place-based leadership for a resilient Thessaloniki, 2011-2021. (December 2022) - Lekakis, Nikos; Liddle, Joyce
Abstract: The 2008 global financial crisis intensified our focus on the role of local governments as strategic actors, within current cycles of economic, political and governance change. This paper highlights the significance of Greece's second-largest city, Thessaloniki, becoming a resilient local authority, with the capacity to respond to perturbations, and the ability to self-organise and learn. Existing models of resilience were insufficient for explaining how a strong mayor's team was able to turn around the fortunes of the city. The paper uses a synthetic theoretical model combining the templates 'behavioural resilience' and 'Place-based leadership'. The findings reveal that Thessaloniki's administration was able to respond to a unique set of problems, including the modernization of local services, balancing a problematic budget, opening the city to the world using some of its historic monuments and drafting an emergency plan for future shocks. The mayor's team was capable of galvanizing a network of key actors from the city's government, public, private and civic bodies to adapt and generate new ways of thinking and functioning in the context of change and uncertainty, so Thessaloniki appeared to offer a role model on how local government in Greece could develop strategies for overcoming austerity and stress.